Triptolide-induced in vitro and in vivo cytotoxicity in human breast cancer stem cells and primary breast cancer cells - LI, JUNJIE; LIU, RUILEI; YANG, YE; HUANG, YONG; LI, XI; LIU, RUIMING; SHEN, XIAOYAN (Oncology reports, 2014)
We investigated the potential efficacy of the Chinese herbal extract triptolide for the treatment of human breast cancer by measuring the triptolide-induced cytotoxicity in cultures of human primary breast cancer cells (BCCs) and breast cancer stem cells (BCSCs) in vitro and in vivo. Human BCCs and BCSCs from invasive ductal carcinoma samples were cultured and treated with 0.1, 0.5 or 1.0 μM triptolide. Cell death and apoptosis were measured after 24, 48 and 72 h of treatment. Mammospheres were found to be highly tumorigenic when implanted subcutaneously in nude BALB/c mice. Triptolide was cytotoxic against both human primary BCCs and BCSCs in vitro (P<0.05), but the cytotoxicity was stronger against the BCCs. In response to 1 μM triptolide for 72 h, the apoptotic rates were approximately 60% for BCCs and 30% for BCSCs. The BCSCs exhibited a high formation rate of tumors when implanted subcutaneously in nude BALB/c mice. Triptolide treatment in vivo significantly inhibited tumor growth compared with mock treatment. In conclusion, the cytotoxicity of triptolide against BCCs and BCSCs in vitro and in vivo suggests that this natural diterpenoid triepoxide compound may have clinical applications for the suppression of breast tumor growth.